The Effect of Unplanned Pregnancy on Postpartum Depression: A Meta-Analysis - Salsabilla, Dinda Anindita; Prasetya, Hanung; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: World data shows that depress